The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.893267
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nutrition Literacy and Overweight/Obesity of Adolescents: A Cross–Sectional Study in Chongqing, China

Abstract: ObjectiveThe burden of overweight and obesity in adolescents is increasing rapidly. This study aimed to assess the association between nutrition literacy and overweight/obesity among adolescents in China.MethodsThis cross–sectional online study involving adolescents aged 10–18 years was conducted in September 2020 in 239 schools in Chongqing China. Overweight and obese adolescents were determined based on the International Obesity Task Force's recommended age–sex specific body mass index cutoff points. Nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
14
0
2
Order By: Relevance
“…There are many studies addressing nutrition literacy and weight status. However, the results of these studies were inconsistent (2,11,42,43) . In some studies, nutrition literacy was inversely associated with overweight/obesity among adolescents (43) , while in others a positive relationship between nutrition literacy and BMI has been reported (11) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are many studies addressing nutrition literacy and weight status. However, the results of these studies were inconsistent (2,11,42,43) . In some studies, nutrition literacy was inversely associated with overweight/obesity among adolescents (43) , while in others a positive relationship between nutrition literacy and BMI has been reported (11) .…”
Section: Discussionmentioning
confidence: 98%
“…However, the results of these studies were inconsistent (2,11,42,43) . In some studies, nutrition literacy was inversely associated with overweight/obesity among adolescents (43) , while in others a positive relationship between nutrition literacy and BMI has been reported (11) . This study showed no association between nutrition literacy and BMI, neck, waist, and hip circumference.…”
Section: Discussionmentioning
confidence: 98%
“…Since health literacy is a general construct, these more specific constructs could be more appropriate in predicting healthy food intake and obesity. In fact, some studies have already related nutrition literacy and food literacy to these outcomes [ 43 , 44 , 45 , 46 ]. More research, comparing the predictive value of health literacy and food/nutrition literacy, is certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed the influence of parents’ health literacy on children’s food intake [ 39 , 40 , 41 ]. More recently, since health literacy is a general construct, the constructs of food literacy and nutrition literacy emerged [ 42 ] and evidence showed an association between food/nutrition literacy and obesity [ 43 , 44 ] and fruit and vegetable consumption [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to many solid evidences, NL has appeared as a critical factor in promoting and maintaining healthy dietary practices among adolescents, including food label use (7), higher dietary diversity (8), and nutrient intake adequacy (8). In addition, a higher prevalence of overweight and obesity was observed among nutritionally-illiterate adolescents (9). Not only improving nutrition outcomes but advocating for better FL and NL could help build resilience against food insecurity (FI) (10).…”
mentioning
confidence: 99%